Aerodynamics of badminton shuttlecock : Characterization of flow around a conical skirt with gaps, behind a hemispherical dome - Lin, C. S. H. (2014)
The effects of gaps on flow properties were studied for thin walled conical structure behind a hemispherical dome- badminton shuttlecocks . Computational fluid dynamics was applied to six different profiles with differing gap sizes. The gaps increased the drag force over a gapless conical skirt by up to 45.2% using the design dimensions. This is termed the critical gap size. Below the critical gap size, drag increases with as gap widens. Beyond the critical gap size, larger gaps resulted in reduced blunt body effect, reduced drag, and increased skirt porosity. Bleeding caused the formation of air jets that diminished the recirculation typical in wake behind a blunt body. Analysis of the pressure profiles showed that gaps increased the differential pressure between the inner and outer surface, thereby producing more drag. The gaps also resulted in spikes along the pressure profiles. Some of the numerical results were validated against wind tunnel experiments. The numerical and experimental results showed good agreement.